2016
DOI: 10.1021/acs.jmedchem.6b00818
|View full text |Cite
|
Sign up to set email alerts
|

New Broad-Spectrum Antibacterial Amphiphilic Aminoglycosides Active against Resistant Bacteria: From Neamine Derivatives to Smaller Neosamine Analogues

Abstract: Aminoglycosides (AGs) constitute a major family of potent and broad-spectrum antibiotics disturbing protein synthesis through binding to the A site of 16S rRNA. Decades of widespread clinical use of AGs strongly reduced their clinical efficacy through the selection of resistant bacteria. Recently, conjugation of lipophilic groups to AGs generated a novel class of potent antibacterial amphiphilic aminoglycosides (AAGs) with significant improved activities against various sensitive and resistant bacterial strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 112 publications
(254 reference statements)
4
36
0
Order By: Relevance
“…It is found that the CS‐adsorbed PP film shows a new band at 1554 cm −1 corresponding to the NH bending vibration, which decreases when CS amino groups interact with the AgNP surface for the AgNP x /CS‐coated PP film. This behavior agrees with the fact that the coordination complex limits the NH vibrational mode and its intensity decreases . The surface functional groups of AgNP x /CS‐coated PP films were also analyzed from the absorbance band ratio from the amino to the methylene group (A15560.62emcm1/A14560.5emcm1).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…It is found that the CS‐adsorbed PP film shows a new band at 1554 cm −1 corresponding to the NH bending vibration, which decreases when CS amino groups interact with the AgNP surface for the AgNP x /CS‐coated PP film. This behavior agrees with the fact that the coordination complex limits the NH vibrational mode and its intensity decreases . The surface functional groups of AgNP x /CS‐coated PP films were also analyzed from the absorbance band ratio from the amino to the methylene group (A15560.62emcm1/A14560.5emcm1).…”
Section: Resultssupporting
confidence: 76%
“…The antimicrobial activity can be imparted to materials employing compounds that reduce or inhibit the growth of microorganisms, without showing general toxicity in the surroundings of the treated center . The antibacterial agents (antibiotics) most commonly used come from completely natural products, such as aminoglycosides; chemically modified natural compounds, such as penicillin, cephalosporin, or carbapenem; and completely synthetic ones, such as sulfonamides . However, the widespread use of these substances and their abuse have led, in many cases, to bacterial resistance, a growing issue that calls for the development of new strategies .…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicate that conjugate 3 enhanced the cellular permeation of novobiocin in P. aeruginosa through outer membrane permeabilization. Alternatively, conjugate 3 may also block the efflux of novobiocin in P. aeruginosa as it is a good substrate for the MexAB‐OprM and MexCD‐OprJ tripartite efflux system . This could be achieved either by cytoplasmic membrane depolarization or by altering the lipid composition surrounding the transmembrane domain of efflux pumps.…”
Section: Resultsmentioning
confidence: 99%
“…Aminoglycosides incapacitate pathogens via inhibition of protein synthesis at low concentrations while membrane disruption occurs at high concentrations . Similarly, amphiphilic aminoglycosides are known to disrupt bacterial membranes . Moreover, we recently reported that some amphiphilic aminoglycosides may possess beneficial immunomodulatory properties .…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity of the materials was evaluated using a MTT assay against Peripheral Blood Mononuclear cells (PBMC) and MCF-7 breast cancer cells to determine cell metabolic activity. 59,61 Aer attainment of 70% conuence the cells were seeded in 96 well plates at a density of 0.3 Â 10 4 cells per well aer which they were treated with materials at different concentrations and incubated at 37 C with 5% CO 2 atmosphere for 24 h. Aer 24 h of incubation, MTT at 5 mg mL À1 is transferred to each well and the whole system is incubated for 3 h at 37 C. The incubation is terminated by recording the absorbance of cells at 590 nm using a UV-Vis Spectrophotometer (Version 2.00, Agilent Technologies Cary 60). All experiments were carried out in triplicate and the results are obtained reported as the mean AE standard deviation.…”
Section: Cytotoxicity Determination Assaymentioning
confidence: 99%